Penggunaan System Application and Product in Data Processing (SAP) dalam Pengelolaan Data Arsip pada Bagian Keuangan PT Telkom Witel Sumbar - Yona, Oktri; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This paper discusses archive management system using System Application And Products In Data Processing (SAP) in the Keuangan PT. Telkom Witel Sumbar. The purpose of this paper is (1) to describe how the records management system using SAP at the Keuangan PT. Telkom Witel Sumbar; (2) Describe any obstacles encountered in the process of using the SAP records management at the Keuangan PT. Telkom Witel Sumbar; (3) describe the efforts made to overcome the obstacles in the process of using the SAP records management at the Keuangan PT. Telkom Witel Sumbar.The method used in this study were collected through a literature review, observation, interviews, and direct observations at Keuangan PT. Telkom Witel Sumbar.Based on the contents of this paper, we can conclude the following: First, the archive storage system at the Keuangan PT. Telkom Witel Sumbar using System Application And Products In Data Processing (SAP) the application used in the management of financial records in order retrieval easier to search the archive. Second, obstacles encountered, namely: (1) the completeness of data entry and the deadline that requires discipline users; (2) is too cumbersome and slow to use; (3) operates on a single database. Third, efforts are being made to overcome the obstacles, namely: (1) the user should be professional and be more careful in managing the archive that will be at the entry to the SAP; (2) has a smart and qualified employees in order in records management using SAP is not slow and cumbersome to be used; (3) using an application that uses a database that can operate much more.Keywords: system applications; management; archival data